KOMPOSISI MUSIK BUBARAN LEAR KOMPOSER RAHAYU SUPANGGAH - Dandun Danurwendo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2014)
This study describes the music composition of Bubaran Lear. Bubaran Lear is a work of musical composition created by Rahayu Supanggah. This study describes the journey of Bubaran Lear from stage to stage. This study emphasizes the staging associated with changes and developments Bubaran Lear. All performances are related to Bubaran Lear not been able to presented in this study, but there is a phase where dispersal lear changing and evolving. The phase includes performances in Bedaya Kartini, King Lear, the film Opera Jawa, Taklim’s concerts, and Opera Jawa Tusuk Konde. Until now, the composition of dispersal lear still growing and developing. Beginning only of the order of tones flowing to get vocal collaboration therein. In this paper also describes the musical inspiration of the musical composition. According to its creator, dispersal Lear inspired by ketawang Undur-Undur Kajongan. Undur-Undur Kajongan a pretty song tradition maintained. Ketawang Undur-Undur Kajongan one selected musical works and still maintained as one of the musical special in the palace compound of Surakarta. When present ketawang Undur-Undur Kajongan only used in the king’s memorial and sung only once a year. This study also describes something that becomes an element of inspiration received composers to become a musical composition Bubaran Lear.Keywords: music composition, Bubaran Lear, Rahayu Supanggah